Factors influencing behavioral intention to use computers among teachers - Ling, L.W. (Institute of Electrical and Electronics Engineers Inc., 2016)
Since the first computer system was implemented in Malaysia in 1996, computers were deployed to schools in Malaysia. Teachers are expected to use the computers in classrooms to accomplish the country's vision to reach the level of a world class quality education system by the end of year 2020. Unfortunately majority of them are not using it as teaching tool in the classrooms. Factors influencing computer usage using The Unified Theory of Acceptance and Use of Technology model (UTAUT) have already been carried by a large number of researchers in Western countries. As many studies had not been conducted based on the Eastern cultural context, an in-depth study on the UTAUT model was carried out to test its applicability in Malaysia. The researchers also make an effort to identify and predict all those factors that show influence on teachers' behavioral intention (BI) in using computers. 40 teachers in Perak were selected to determine whether the 4 UTAUT main constructs; Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI) and Facilitating Conditions (FC) have an impact on the teachers' BI to utilize computers in classrooms environment. This study also introduces an extra construct in the modified UTAUT conceptual model, 'Perceived Needs'. Confirmatory factor analysis (CFA) has been engaged in order to determine the modified UTAUT model's reliability and validity. Findings from this study depicted that Perceived Needs is also a crucial factor influencing teachers' behavioral intention of utilizing the computer. Â© 2016 IEEE.